THE EFFECT OF SPECIAL EXERCISES IN ACCORDANCE WITH INTEGRATION WITH NORMAL PEOPLE ON THE PERFORMANCE ENDURANCE OF PEOPLE WITH MILD MENTAL DISABILITIES IN FUTSAL - Shneair, Thaer Saleh; Ghali, Abed Sarwal (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
Providing rehabilitation programs for the disabled instead of isolating them has a significant impact on developing and improving all mental and physical abilities and capabilities, thus helping the disabled individual to overcome some problems by recovering the maximum possible of their potential in life through integration with normal people and developing the learning and comprehension process effectively and quickly with the least time and effort for the disabled individual and providing special training programs away from isolation and restrictions imposed on them by society in a natural and non-isolated environment, thus eliminating the feeling of frustration and shock when failing to perform or improve and being pursued by these consequences, as well as improving the feeling of society in general towards the disabled and their abilities and increasing confidence in them and even forming friendships by integrating them with normal people and reducing the differences between them and providing services and helping them by directing them on ways to deal with society and the environment surrounding them, and through activities, events, training and sports competitions with normal people that develop the spirit of competition in an effective and strong way, here the level of the disabled can develop in a better and more beneficial way than in isolation from normal people, so the researchers saw that it should be the starting point for addressing the problem Slow development of the disabled through integration into performance and training for special exercises with healthy people to reduce the differences in the speed of development and improvement of the disabled player compared to his healthy counterpart by improving physical and skill performance and for the sake of athletic excellence and reaching distinguished levels globally in the field of Futsal for this category.